Prevalence, associated factors and etiologic agents of oral candidiasis among HIV-positive patients in a Vietnamese general hospital - Canh, Hoang Dinh; Tham, Ngu Thi; Tram, Que Anh; Loi, Cao Ba; Tran-Anh, Le (Current medical mycology, 2024)
Oral candidiasis (OC) is a common condition in HIV-infected individuals. This study aimed to identify the prevalence, associated factors, and causative agents of OC among HIV-infected patients in a general hospital in Vietnam. The study involved 393 HIV-infected individuals treated at The Tropical Diseases Center, Nghe An General Friendship Hospital, Vinh, Nghe An, Vietnam from January 2022 to May 2024. The sample collected from the buccal mucosa was seeded onto CHROMagar to isolate and identify the causative yeasts. Molecular identification was performed with restriction fragment length polymorphism assay using MspI restriction enzyme and sequencing of the internal transcribed spacer (ITS) region. The prevalence of OC was 10.7% (95% confidence interval 7.6 - 13.8). Patients with late WHO HIV clinical stage, poorer hygienic condition, or use of prosthetic were at a higher risk of OC. Ten yeast species were isolated, and 10 (23.8%) patients carried more than one type of yeast species. Out of 54 obtained isolates, comprised the most (62.9% isolates and 80.9% patients), followed by (16.4% and 21.4% respectively). Overall, 27 patients (64.3%) were infected with , and 15 patients (35.7%) were infected with non- , alone or in combination with The prevalence of OC in HIV-infected patients was low and associated with both systemic and local factors. was still the most common species but non- or coexistence of species is frequent.